Look, I made a hat collected lyrics (1981 - 2011) with attendant comments, amplifications, dogmas, harangues, digressions, anecdotes and miscellany - Sondheim, Stephen 1930-2021 (A Borzoi book, 2011)
Picking up where he left off in "Finishing the Hat", Sondheim richly annotates his lyrics with personal and theatre history, discussions of his collaborations, and exacting, charming dissections of his work -- both the successes and the failures